Antibiotics Susceptibility Profile of Gram-Positive Bacteria from Primary Health Centers in Jega, Kebbi State - Bilyaminu Garba Jega; Isa Musa Maishanu; Basiru Aliyu; Mohammed Ndagi Kasim (Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Nosocomial or healthcare-associated infection (HCAI) is an infection acquired during receiving health care that was not present during the time of admission. The research aimed to determine the antibiotic susceptibility pattern of gram-positive bacteria isolated from Primary Health Centers in Jega Town. A total of fifty (50) swab samples were collected from 10 different health centers and analyzed using the streak plate technique. Pure bacterial isolates were maintained and characterized using biochemical tests; their percentage of occurrence show; Staphylococcus aureus 18 (43.9%), Enterococcus feacalis 8 (19.5%), Streptococcus spp 8 (19.5%), Bacillus cereus 4 (9.8%), and Staphylococcus epidermis 3 (7.3%). McFarland standard solution was prepared and used to control inoculants, after which the antibiotic susceptibility pattern of the isolates was determined using the disc diffusion method. The Staphylococcus epidermis was found resistant to Gentamycin, and other isolates were multi-drug resistant. In the light of this research, there is a need for thorough disinfection and conscientious contact control procedures to minimize the spread of these pathogens in the health centers where interaction between patients, HCWs, and caregivers is widespread and frequent.